Penile reconstruction post-oncologic surgery: comprehensive approaches - F., Fernández-Varela-Gomez; Anceno-Olivares, Alec; Jiménez-Marco, María Fernanda; Salas-Vázquez, María Natividad; Flores-Pérez, Fidel Iván; Nuñez-Castellanos, Luis Enrique (International Surgery Journal, 2024)
Post-oncologic penile reconstruction aims to restore penile form and function following surgical resection due to penile cancer. This reconstructive surgery is essential as treatments like partial or total penectomy can severely impact a patient’s quality of life. The primary goals include maintaining urinary and sexual function while achieving a cosmetically acceptable result. Techniques range from simple resurfacing of the glans to complex procedures like phalloplasty, while penile-sparing therapies, including topical treatments and laser ablation, are also used to minimize disfigurement. Penile cancer, predominantly squamous cell carcinoma, is rare but more prevalent in developing countries, with risk factors such as human papillomavirus (HPV) infection and poor hygiene. The preoperative evaluation involves assessing comorbidities, psychological state, and functional capacity to ensure optimal outcomes. Criteria for reconstruction include the extent of the defect, oncological status, and desired outcomes. Techniques employed in reconstruction include local, inguinal, anterolateral thigh, and myocutaneous flaps, as well as grafts and alloplastic materials. Innovations in surgical methodologies and multidisciplinary strategies have significantly improved outcomes. However, complications, including high perioperative morbidity, underscore the need for careful patient selection and management. Psychosocial support is crucial for optimal recovery and quality of life, emphasizing the importance of a comprehensive, patient-centered approach in post-oncologic penile reconstruction. This holistic approach ensures that patients not only achieve cancer survival but also maintain a high quality of life following their treatment.